International Law Enforcement Against Drug Smuggling in Indonesia - Aryono, Aryono; Saputro, M Susilo Agung (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Enforcement of international law against drug smuggling in Indonesia. Drug smuggling is a serious issue that affects the country's social and economic stability. Indonesia, as a country that has the widest borders with other countries, is an important point in regional drug movements. International law plays an important role in enforcing laws against drug smuggling, but its implementation in Indonesia still faces various challenges. This journal examines how international law is applied in the Indonesian context, including the role of the government, international institutions and society in enforcing the law against drug smuggling. Apart from that, this journal also explores the impact of drug smuggling on Indonesian society and the strategies that can be implemented to overcome this problem. The research results show that international law enforcement requires close cooperation between various parties, including the government, international institutions, and society. This journal hopes to provide new insights into how international law can be more effective in law enforcement against drug smuggling in Indonesia.